The Principle of Legal Certainty and Retroactive Tax Penalties: A Doctrinal Dilemma in Fiscal Criminal Law - Hartanto, Anton (Journal of Tax Law and Policy, 2025)
Tax law plays a central role in ensuring state revenue and regulating economic activity. The principle of legal certainty serves as a crucial foundation in the tax law system, as it guarantees that tax regulations are predictable and non-retroactive. However, the application of retroactive tax sanctions has sparked serious debate within fiscal criminal law, particularly because it potentially violates the principle of legal certainty, which is constitutionally guaranteed in Indonesia. This study employs a doctrinal approach to examine three key issues: (1) the alignment between retroactive tax sanctions and the principle of legal certainty; (2) the legal and doctrinal frameworks that permit the retroactive application of tax laws; and(3) specific circumstances that may justify retroactivity without infringing upon legal certainty. The study finds that although criminal law in principle rejects retroactivity, limited justification for retroactive tax sanctions exists in cases such as legislative corrections, tax avoidance, or voluntary disclosures. Nonetheless, retroactive application must meet standards of proportionality, the protection of legitimate expectations, as well as transparency and judicial oversight, to ensure its conformity with legal principles and the protection of taxpayer rights.